KEJADIAN MENOPAUSE PADA IBU DENGAN RIWAYAT KB SUNTIK 3 BULAN DI WILAYAH KERJA BPM DWI MINARSIH DESA NGEMBEH KECAMATAN DLANGGU KABUPATEN MOJOKERTO - Zainuri, Imam; Robibah, Luluk (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Menopause is the last menstrual periodof a womenand is the diagnosis enforced retrospective after amenorrhea for 12 months. The purpose of this study is to determine the menopause occurrence description of the mother with 3 months of injection family planninghistory at the work area of Dwi Minarsih BPM Ngembeh village sub district Dlanggu district Mojokerto in 2014. The study design used in this study is descriptive. All menopausal mothers with 3 months of injection family planninghistory at the work area of Dwi Minarsih BPM Ngembeh village sub district Dlanggu district Mojokerto. The sample consisted of 43 respondents. The sample selection is done by accidental sampling. The study variable is the menopause occurrencedescription of the mother with 3 months of injection family planninghistory. The results presented is the table of frequency distribution. The result of data analysis showed the majority of menopausal mothers with 3 months of injection family planning history at the work area of Dwi Minarsih BPM Ngembeh village sub district Dlanggudistrict Mojokerto in 2014 experienced the latest menopause (72.09%). From these results can be concluded that the majority of menopausal mothers with 3 months of injection family planning history at the work area of Dwi Minarsih BPM Ngembeh village sub district Dlanggu district Mojokerto experienced the most late menopause. Health workers are expected to be participatory in outreach to the society, especially the women is regarding physical and psychological problem that may arise in line with the onset of menopause so the societywill understand more and knows about the complaint before menopause.Keywords:mother, menopause, 3 monthsof injectionfamily planning